2015
DOI: 10.5530/ijopp.8.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance of Drug Information Service and Drug Therapy Review Provided by Clinical Pharmacists in an Indian Teaching Hospital

Abstract: Background: To ensure the competent delivery of patient care by clinical pharmacists, it is essential to evaluate services provided by them. Objectives: This study was conducted to assess the impact of Standard operating procedure (SOP) on quality of Drug information (DI) service and drug therapy review provided by clinical pharmacy department. Methods: The study was conducted at department of clinical pharmacy located at tertiary care teaching hospital. Quality assessment checklist was designed to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…But Mahendrakumar BJ et al, and Himanshu P et al, conducted a study showed that maximum numbers of queries were on dosage and administration. 12,13 180 85…”
Section: Resultsmentioning
confidence: 99%
“…But Mahendrakumar BJ et al, and Himanshu P et al, conducted a study showed that maximum numbers of queries were on dosage and administration. 12,13 180 85…”
Section: Resultsmentioning
confidence: 99%
“…Patel et al 6 performed quality assurance of drug information service and drug therapy review without any external expert in the panel. However, checklist of quality assurance of clinical pharmacy service was similar to present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important to procure accurate unbiased information. In India, irrational use of drugs is common and this has led to antibiotic resistance, adverse drug reactions, drug interactions and other drug related problems [3][4][5][6] . Among the many factors that make clinicians unable to update their knowledge about drugs, lack of unbiased drug information, availability of more than 60,000 formulations and lack of time are few notable reasons which ultimately lead to an increasing demand for independent, specific and unbiased drug information for better patient care [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Interventions: Ensuring the competent delivery of patient care by clinical pharmacists towards the patients was scarcely acquired and it paramount the most to evaluate services provided by them regarding the awareness about the predisposing factors of the diseases 3 . Findings suggest that endemic infectious and non-infectious disease research publications that explicitly or implicitly incorporate social epidemiological approaches have stagnated in recent years 4 .…”
Section: Fig 4: Percentage Of Particular Disease With Co -Morbiditymentioning
confidence: 99%
“…Epidemiological studies have played an important part in the elucidation of predisposing factors for COPD, CKD, acute pancreatitis and CLD and opportunities for prevention and treatment 2 . The present study is designed retrospectively to focus on prevalence of various COPD, CKD, acute pancreatitis and CLD and causes of mortality in patients admitted to respective speciality units 3 .…”
mentioning
confidence: 99%